Tobacco use among in-school young adolescents in Indonesia: Exploring availability, affordability, and accessibility. - Yeni Rosilawati; Zain Rafique; Erwan Sudiwijaya (PLoS ONE)
The research on Indonesian adolescents' perception of tobacco control in schools is limited. This study aimed to explore the availability, affordability, and accessibility of tobacco among young adolescents in Yogyakarta Municipality, Indonesia, with a focus on advocating for school teenagers. Focus groups, comprising participants from diverse backgrounds and stakeholders, were conducted in Yogyakarta, Indonesia, to systematically collect varied data. The subsequent analysis employed a robust thematic approach, combining both inductive and deductive processes to ensure a nuanced exploration of emerging patterns and pre-existing frameworks. In addition to focus group data, the study incorporated insights from extensive field observations and research group discussions. The multifaceted approach enhanced the depth of analysis but also facilitated a comprehensive understanding of the complex dynamics. The findings of this study revealed that young adolescents found it extremely easy to purchase cigarettes from local markets. The smoking prevalence among young adolescents was relatively low, with only 10% of the respondents admitting to smoking. Although the Indonesian government has increased surveillance and regulations regarding smoking among young individuals, the actual implementation and effectiveness of these measures remain questionable. The existing anti-smoking approaches in Indonesia have been unsuccessful in curbing smoking among Indonesian school students. The study argues that it is crucial to recognize and value students' perceptions of smoking, as their knowledge of smoking is actively constructed. To address this issue, future anti-smoking education in schools should incorporate interactive sessions rather than solely relying on didactic approaches that highlight the harms of smoking. By engaging students in interactive discussions, they can actively participate in constructing their understanding of the consequences of smoking. Additionally, efforts should be made to enhance the implementation of tobacco control measures within schools and extend the reach of these measures to off-campus environments.